Adeno-associated virus vector-based gene therapy for hereditary diseases: current problems of application and approaches to solve them - T. V. Egorova; A. A. Piskunov; D. A. Poteryaev (Биопрепараты: Профилактика, диагностика, лечение, 2024)
INTRODICTION. Currently, gene therapy based on adeno-associated virus (AAV) vectors faces a  number of barriers, both biomedical and technological, which require studying and overcoming for further development of this gene therapy technology.AIM. This study aimed to analyse the use of gene therapy for a range of hereditary diseases, taking into account the barriers associated with its side effects and insufficient efficacy, the determination of the therapeutic window, and individual characteristics relevant to a particular hereditary disease; additionally, the study aimed to review the approaches to lifting these barriers and increasing the availability of gene therapy through the improvement of technological approaches to production and the reduction of production costs.DISCUSSION. The authors reviewed the experience accumulated for gene therapy products that were approved or undergoing clinical trials. The study included a gene therapy applicability assessment using several hereditary diseases as a case study. The assessment showed that correct determination of the therapeutic window for a medicinal product and timely diagnosis of a hereditary disease were essential for effective and safe gene therapy. The study considered the strategies used to reduce the risks of adverse events and increase the effectiveness of AAVbased gene therapy. The authors assessed technological advancements in the manufacturing of AAV-based gene therapy products. The most perspective directions were the transition to suspension culture systems, the improvement of bioreactors, the use of new methods and materials for the purification of viral particles, the improvement of transfection systems, and the creation of new host cell lines. Ultimately, this can lead to lower production costs and an increased availability of gene therapy.CONCLUSION. Currently, gene therapy is used only for a small range of hereditary diseases. Significant barriers to its use are due to insufficient efficacy, risks of adverse events, and high costs for treatment. Ongoing biomedical and technological development should lift many of these barriers and increase access to gene therapy.